Reviving Underutilized Agricultural Lands for Sustainable Land Use: A Case Study of Valigamam North, Jaffna District - Kokulavarnan, K.; Thanushan, R. (Faculty of Arts, University of Jaffna Sri Lanka, 2025)
The prolonged civil conflict in Sri Lanka led to the displacement of communities in Valigamam North, Jaffna during the 1990s. As a result, highly productive agricultural lands in the region remained unused for approximately 26 to 30 years. Although these lands are now gradually being returned to the original inhabitants, agricultural utilization remains low, particularly in areas such as Kankesanthurai area, Palali and Vasavilan village. This study investigates the barriers to effective agricultural land use in Valigamam North and explores strategies for promoting sustainable agricultural practices. Primary data were collected through direct field observations, focus group discussions with 95 residents in 25 groups and in-depth interviews with 20 stakeholders, including local residents, political activists and farmers. Secondary data were obtained from Divisional Secretariat records, land ownership documents and reports from Grama Niladhari officers. Field observations revealed that many agricultural lands are located within High Security Zones, particularly in Valigamam North, limiting their use. In Kankesanthurai area, lands are enclosed by fences and pillars and are overrun by invasive species such as weeds and Parthenium hysterophorus, making them unsuitable for cultivation. In Palali and Vasavilan village, former agricultural lands have transformed into an invasive alien species Ippil-Ippil (Leucaena leucocephala) forest, while other areas contain extensive limestone outcrop deposits due to past soil excavation. Quantitative findings show that 68% of residents are not using their agricultural lands due to military restrictions, especially the presence of security fences. Additionally, 96% are affected by the lack of essential infrastructure, including housing, roads, wells and electricity. 52% are constrained by security concerns such as stealing, wild animal damage and the risk of landmines. War-related factors such as displacement, lifestyle changes and migration affect 52% of respondents. Moreover, 48% of the population refrains from using agricultural lands for cultivation due to economic factors such as increasing land prices and the declining profitability of agriculture. Thematic analysis confirms that only certain pockets of land are under cultivation, while vast areas remain underutilized. To address these challenges, the study recommends that the government prioritise the development of infrastructure, remove remaining security fences and provide subsidies and credit assistance to farmers. Farmers should be encouraged to adopt modern agricultural techniques and seek out emerging market opportunities. Non-governmental organizations (NGOs) should support this transition by offering technical training, awareness programmes and marketing assistance. These combined efforts aim to foster both short-term agricultural recovery and long-term sustainable land use, ultimately contributing to the comprehensive agricultural revival of Valigamam North.
Keywords: Agricultural land abandonment; Military restrictions; Land degradation; Sustainable farming; Post-conflict recovery; Valigamam North